E-044 Capitated pricing model for stroke thrombectomies: a single institution experience. (4th August 2020) - Shah, K; Brown, M; Desai, S; Jankowitz, B; Jovin, T; Jadhav, A; Gross, B
Abstract : Introduction: With a continued rise in health care expenditures, there is a demonstrable focus on curbing expenses. Recent studies estimate direct and indirect costs of stroke to be $73.7 – 103.5 billion 1, 2 . Since 2015, numerous studies demonstrate the benefit of mechanical thrombectomy (MT) for treatment of large vessel occlusions (LVOs) 3–10 ; however, notable costs are associated with devices utilized in each procedure. Some institutions have negotiated capitated pricing models in an effort to reduce these costs; however, the cost savings has yet to be critically evaluated. Materials and Methods: We reviewed mechanical thrombectomy cases performed at University of Pittsburgh Medical Center's (UPMC) Presbyterian and Mercy hospitals between February 2018 and August 2019, identifying those meeting criteria under capitation models negotiated with Companies A, B, and C (table 1 ). We calculated the cost of equipment for each thrombectomy using the negotiated cost for individual devices utilized and compared this sum to the total derived from cost-negotiated bundled equipment packages, resulting in the difference between non-capitated and capitated cost. Results: 107 cases were identified as meeting the criteria for capitation under the negotiated contracts; 39 cases using Company A (28 using stentrievers), 44 cases using Company B (3 using stentrievers), and 24 cases using Company C (14 using stentrievers). Total cost of equipment with the capitated model was $689, 435 compared to $891, 805.50 with the non-capitated model, a difference of $202, 370.50. This amounted to $1, 891.31 savings per case. Mean capitation model equipment costs were $1, 245.26 [$570.00 – $7, 670.00], $1, 110.80 [$165.00 – $5, 755.00], and $4, 372.10 [-$64.00 – $16, 116.00] lower per case than non-capitation for Companies A, B, and C, respectively. The variation in cost savings between companies relates to multiple devices utilized that raise non-capitated costs. When combining the stentriever and non-stentriever bundles, irrespective of company, the capitated model yielded $2947 ± 3759 and $1124 ± $1330 savings compared to the non-capitated model, respectively. Conclusion: Overall, at our institution, the negotiated capitation model yielded total cost savings, savings within each company, and with bundles including or not including stentrievers. This may serve as a model for other centers in controlling costs for patients undergoing MT for LVO. Disclosures: K. Shah: None. M. Brown: None. S. Desai: None. B. Jankowitz: 2; C; Medtronic. T. Jovin: 2; C; Stryker Neurovascular (PI DAWN - Unpaid), Blockade Medical. 5; C; Anaconda, FreeOx Biotech, Route92. 6; C; Honoraria: Cerenovus. A. Jadhav: None. B. Gross: 2; C; Medtronic, Microvention.